COMPARATIVE PROBIOTIC ACTIVITY AGAINST STREPTOCOCCUS PYOGENES. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation. This article presents the results of studying the activity of two probiotic drugs of Russian origin Lactobacterin+, Sporobacterin, one probiotic created by employees of the Samarkand state university of veterinary medicine, livestock and biotechnology - Innoprovet2 and the antibiotic ciprofloxacin, which demonstrated high antimicrobial activity against the pyogenic microbe Str.pyogenes isolated from abscesses of cattle. A comparative study showed that all probiotics showed high antimicrobial activity equal to antibiotic activity.